Vertical structures of raindrop size distributions over the middle and lower reaches of Yangtze River during the Meiyu period in 2020 - Lingli ZHOU; Zhikang FU; Guirong XU; Jixin WANG; Bin WANG (暴雨灾害, 2023)
Droplet size distribution (DSD) is an important parameter reflecting microphysical characteristics of rainfalls, research on vertical structures of DSD is helpful to understand rainfall evolution processes and improve radar quantitative precipitation estimations. Vertical structures of DSDs under different rain rates over different regions during the Meiyu period in 2020 have been investigated using the co-located two-dimensional video disdrometer (2DVD) and micro rain radar (MRR) at the stations of ZiGui, JingZhou and NanJing. It is found that, when raindrops fall, the number concentration of small raindrops and their contribution to rain rates decrease, while the number concentration of medium and large raindrops and their contribution to rain rates increase, which finally leads to that medium raindrops contribute most significantly to surface rain rates. Vertical structures of DSDs under different rain rates are different. For weak rainfall, there are narrow DSDs and the equilibrium of raindrop evaporation and coalescence causes small variation in DSD parameters. For heavy rainfall, there are significantly widened and increased DSDs, because obvious collision process increases the concentration of medium-large raindrops when raindrops falls and thus causes large variation in DSD parameters. Statistical analysis shows that DSDs present significant difference over different regions: the highest number concentration and the smallest raindrop diameter at ZiGui, medium number concentration and medium diameter at Jinzhou, the lowest number concentration and the largest diameter at Nanjing. Moreover, μ-Λ relationships present regional difference, and the fitted values of rain rates with local Z-R relationships over different regions agree well with the observations of 2DVD.